Adaptation and initial validation of student stress inventory for use among Malaysian secondary school students - Abdul Kudus, Farah Nadiah; Shamsul, Nur Syazera; Abd Rahman, Shukran (IIUM Press, International Islamic University Malaysia, 2020)
The paper discusses the process to adapt the Student Stress Inventory (SSI) and reports the finding of its content validation. The process entailed, firstly, forward and backward translation of items to be used in a new population of test takers whose culture is different from that of the original SSI standardisation sample. The translation process was accomplished by subject matter experts (SMEs) who are well-versed in the English and Malay languages. They too understand the nature and extent of culture in the destination and original culture. The second stage is the item verification process in which five SMEs (Clinical Psychologist, Counsellor, Linguist, English teacher, and Parent) verified and provided comments on every item before subjecting them to content and face validation stage. 10 SMEs, who were Psychology graduates, have been engaged to judge if the adapted Malay items are essential in measuring the construct-in-question among the Malay test takers. The SME judgments were calculated to obtain the content validity ratio of each item. Items that do not meet the minimum value of CVR will be further reviewed. Besides, the feedback provided in the validation was used by the researchers to improve the face validity of the items.